The life impossible - Haig, Matt, 1975- (New York : Viking, 2024)
"The remarkable next novel from Matt Haig, the author of #1 New York Times bestseller The Midnight Library, with more than nine million copies sold worldwide "What looks like magic is simply a part of life we don't understand yet..." When retired math teacher Grace Winters is left a run-down house on a Mediterranean island by a long-lost friend, curiosity gets the better of her. She arrives in Ibiza with a one-way ticket, no guidebook and no plan. Among the rugged hills and golden beaches of the island, Grace searches for answers about her friend's life, and how it ended. What she uncovers is stranger than she could have dreamed. But to dive into this impossible truth, Grace must first come to terms with her past. Filled with wonder and wild adventure, this is a story of hope and the life-changing power of a new beginning"--
Keywords: FICTION